Coastline Changes in Vicinity of Runway Platform of Sultan Mahmud Airport, Kuala Terengganu: Comparative Analysis of One-line Model Versus Satellite Data - Mustafa, Mamat; Mohammad Fadhli, Ahmad; Rosnan, Yaacob (2014)
The aim of the research is to quantify the changes of coastline nearby the reclamation of sand for runway of airport Sultan Mahmud, Kuala Terengganu. The reclamation was built towards sea with beach nourishment in order to accommodate the operation of 747-400 aircraft landing at the airport. From the visual observation the offset changes from the original position of shoreline due to erosion was more than 10 m during 2010 to 2011. The numerical method that used for solve coastline case in this research is Littoral Processes and Coastline Kinetics numerical model (LITPACK). The results from the numerical model were then compared and verified with data from satellite. The computation of shoreline evolution was calibrated and validated by changing the bed roughness of the seabed. The method of Root Mean Square Percentage En-or (RMSPE) was performed to find the percentage error of the simulation against the actual data. From the results obtain, it is found that die bed roughness of 0.004 m shows the good agreement with the actual data where the RMSPE is 0.76%. It is also found that the reclamation of sand for runway platform contributes severe erosion on an average of 21.3 m at the north side and accretion on an average of 24.8 m at the south sides of the between in year 2010-2013.